Diffusely appearing white matter in multiple sclerosis: insights from sodium (23Na) MRI - Weber, Claudia Ellen; Nagel, Katja; Ebert, Anne; Roßmanith, Christina; Paschke, Nadia; Adlung, Anne; Platten, Michael; Schad, Lothar R.; Gass, Achim; Eisele, Philipp (Multiple Sclerosis and Related Disorders, 2021)
Background - In multiple sclerosis (MS), magnetic resonance imaging (MRI) frequently shows ill-defined areas with intermediate signal intensity between the normal appearing white matter (NAWM) and focal T2-hyperintense lesions, termed “diffusely appearing white matter” (DAWM). Even though several advanced MRI techniques have shown the potential to detect and quantify subtle commonly not visible microscopic tissue changes, to date only a few advanced MRI studies investigated DAWM changes in a quantitative manner. The aim of this study was to detect and quantify tissue abnormalities in the DAWM in comparison to focal lesions and the NAWM in MS patients by sodium (23Na) MRI. - Methods - 23Na and conventional MRI were performed in 25 MS patients with DAWM (DAWM+) and in 25 sex- and age matched MS patients without DAWM (DAWM−), as well as in ten healthy controls (HC). Mean total sodium concentrations (TSC) were quantified in the DAWM, NAWM, normal appearing grey matter (NAGM) and in focal MS lesions. - Results - In MS DAWM+and DAWM−, TSC values were increased in the NAGM (DAWM+: 44.61 ± 4.09 mM; DAWM-: 45.37 ± 3.8 mM) and in the NAWM (DAWM+: 39.85 ± 3.89 mM; DAWM-: 39.82 ± 4.25 mM) compared to normal grey and white matter in HC (GM 40.87 ± 3.25 mM, WM 35.9 ± 1.81 mM; p < 0.05 for all comparisons). Interestingly, the DAWM showed similar sodium concentrations (39.32 ± 4.59 mM) to the NAWM (39.85 ± 3.89 mM), whereas TSC values in T1 hypointense (46.53 ± 7.87 mM) and T1 isointense (41.99 ± 6.10 mM) lesions were significantly higher than in the DAWM (p < 0.001 and 0.017 respectively). - Conclusion - 23Na MRI is confirmed as a sensitive marker of even subtle tissue abnormalities. DAWM sodium levels are increased and comparable to the abnormalities in NAWM, suggesting pathological changes less severe than in focal lesions comparable to what is expected in the NAWM.
Gesehen am 16.08.2021
Im Text ist "23" hochgestellt